Optimizing the Nutritional Status of Elementary School-Age Children Through Family Counseling About Children's Sleep Quality: a Literature Review: Optimalisasi Status Gizi Anak Usia Sekolah Dasar Melalui Konseling Keluarga Tentang Kualitas Tidur Anak: Literatur Review - Putra, Andhika Satriya; Susanto, Tantut; Susumaningrum, Latifa Aini; Rasni, Hanny; Kurdi, Fahruddin (Jurnal Kesehatan Komunitas Indonesia, 2022)
Sleep quality can be interpreted as a person's satisfaction in his sleep, good sleep quality can make the person feel fresh and fit when he wakes up. Sleep disorders in elementary school children aged 7-11 years in Indonesia as much as 65.3% in 2020. Long term, lack of sleep can cause obesity, depression, and fatigue. Imbalanced nutrition and poor sleep quality lead to inhibition of appetite regulation. Parents have an important role in setting a child's sleep schedule, behavior, and activities. The research design this study was a traditional literature review. The selection of articles in this study used PRISMA Flowchart. Articles searched using search engines (SpringerLink, ScienceDirect, Pubmed, and Google Scholar). Family counseling about the quality of children's sleep can affect the fulfillment of nutritional status. Children's nutritional status is influenced by several factors, such as children's sleep quality, children's physical activity, and children's eating patterns. These three elements must be met so that the nutritional status of children does not decrease and children become overweight or obese. Counseling that can be done is like a "healthy family routine" where it contains the child's sleep hours according to the child's age, the benefits of sleep for children, and parents recognize sleep problems in children, such as external factors (crowd, bed comfort, and noise pollution).